Egg white-mediated green synthesis of CuS quantum dots as a biocompatible and efficient 980 nm laser-driven photothermal agent. Issue 46 (22nd April 2016) - Zhong, Runzhi; Peng, Chen; Chen, Liang; Yu, Nuo; Liu, Zixiao; Zhu, Meifang; He, Chuanglong; Chen, Zhigang
Abstract : CuS quantum dots have been prepared by using chicken egg white as the ligands. After injected with CuS solution, the tumor exhibits a rapid temperature elevation to above 52 °C after 60 s irradiation of 980 nm laser, resulting in the efficient ablation of cancer cells in vivo . Abstract : Near-infrared (NIR) laser-induced photothermal ablation therapy (PAT) has great potential to revolutionize conventional therapeutic approaches for tumors, and a prerequisite is to obtain biocompatible and efficient photothermal agents. CuS nanomaterials have been demonstrated to be good photothermal agents, and they are usually prepared with organics/polymers as the surface ligands at high temperature (50–300 °C). To enhance the biocompatibility and photothermal performance of CuS, herein we develop a green and straightforward method for preparing CuS quantum dots (QDs) by using chicken egg white (CEW) as the surface ligands at physiological temperature (∼37 °C). CuS QDs have the diameter of 7.1 ± 0.6 nm and exhibit strong NIR photoabsorption. Under the irradiation of a 980 nm laser with intensity of 0.44 W cm −2, the CuS QD aqueous dispersions (0.25–1.0 mg mL −1 ) exhibit a temperature elevation of 17.2–37.4 °C in 8 min, yielding a photothermal conversion efficiency of 47.2%. Furthermore, CuS QDs exhibit almost no cytotoxicity on cell growth, due to the good encapsulation by highly nutritional proteins from the CEW. More importantly, under the irradiation of a 980 nm laser (0.44 W cm −2, a low/safe intensity for human skin) for 6 min, cancer cells in vitro and in vivo can be efficiently ablated by the photothermal effects of CuS QDs. Therefore, CuS QDs can be used as a kind of promising, biocompatible and efficient photothermal agent for NIR-PAT of tumors.